2009
DOI: 10.1158/1535-7163.mct-08-0762
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin inhibits pancreatic cancer cell proliferation and tumor progression in a xenograft mouse model

Abstract: Crocetin, a carotenoid compound derived from saffron, has long been used as a traditional ancient medicine against different human diseases including cancer. The aim of the series of experiments was to systematically determine whether crocetin significantly affects pancreatic cancer growth both in vitro and/or in vivo. For the in vitro studies, first, MIA-PaCa-2 cells were treated with crocetin and in these sets of experiments, a proliferation assay using H 3 -thymidine incorporation and flow cytometric analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 39 publications
4
88
0
3
Order By: Relevance
“…Among the cytotoxicity detection experiments, crocetin revealed significant antiproliferative effects on the BGC-823 cells in a dose-and time-dependent manner. It is noteworthy that accumulated data concerning the toxic effect of crocetin has been reported, but there are different standpoints with regard to its effect (14). However, one previous in vitro study observed that crocetin had no cytotoxic effect in the normal cells (23).…”
Section: D a Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the cytotoxicity detection experiments, crocetin revealed significant antiproliferative effects on the BGC-823 cells in a dose-and time-dependent manner. It is noteworthy that accumulated data concerning the toxic effect of crocetin has been reported, but there are different standpoints with regard to its effect (14). However, one previous in vitro study observed that crocetin had no cytotoxic effect in the normal cells (23).…”
Section: D a Bmentioning
confidence: 99%
“…Crocetin, a major active ingredient of saffron extract, has been revealed to possess potent antiproliferative and antioxidative characteristics. Moreover, the antitumor activity of crocetin has been observed to enhance the apoptosis of several types of cancer cells in vitro and inhibit the growth of tumors in vivo, including human liver (12), colorectal (13), pancreatic (14) and breast (15) cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The plant was used as an aphrodisiac, antispasmodic, and expectorant in folk medicine (Abdullaev, 1993;Abdullaev & Espinosa-Aguirre, 2004). In modern medicine, antimicrobial (Aung et al, 2007) and anticancer (Aung et al, 2007;Das et al, 2009;Dhar et al, 2009) effects have been described for its extract. It is now clear that saffron water or alcohol extracts may have anti-anxiety (Pitsikas et al, 2008;Hosseinzadeh & Noraei, 2009) and antidepressant effects (Akhondzadeh et al, 2004;Moshiri et al, 2006;Akhondzadeh Basti et al, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…Many studies have demonstrated various pharmacological effects of saffron and or its important compounds including antioxidant activity, anti tumor, memory and learning enhancing, treatment of hepatic disorders, anti inflammatory, anti depressant and insulin resistant reducing (Sanchez-Vioque et al 2012;Makhlouf et al 2011;Umigai et al 2011;Ghadrdoost et al 2011;Amin et al 2011;Dhar et al 2009;Nkhaei et al 2008;Ochiai et al 2007;Soeda et al 2007;Abdullaev and Espinosa-Aguirre 2004). All these properties have been attributed to the stigmas, the sole commercially valuable part of the plant whereas other parts of the plant have been much less studied.…”
Section: Introductionmentioning
confidence: 99%